THE WORLD'S GREAT WONDERS : HOW THEY WERE MADE & WHY THEY ARE AMAZING - Osman, Jheni, (Lonely Planet Publications, 2014)
Go beyond the visual spectacle of the world's 50 greatest wonders, and discover what makes them such amazing places. With stunning images and expert illustrations, experience and appreciate the most famous sights on earth in an exciting new way.